Penerapan Metode Ripple Down Rules Untuk Mendiagnosa Penyakit Burung - Dahri Musnandar (Universitas Budi Darma, 2020)
Birds or poultry are members of vertebrate animals that have feathers and wings. Diseased birds certainly look different from their normal condition and exhibit strange symptoms, if they are usually agile and active or often chirping, but when they are sick the bird looks limp, and chooses more silence. Of the symptoms that arise there are symptoms that can be seen by the eye or clinically and by looking at these symptoms can be known what diseases attack birds. To get a solution to the disease, a tool or system is needed to do it. The Ripple Down Rule (RDR) method is one method that has expert system inference / search capabilities and knowledge acquisition. By using the RDR method a system will be able to infer or identify several types of diseases suffered by birds as experts with clinical symptoms such as input. Recognized disease data adjusts rules (rules) that are made to be able to match the symptoms of bird disease stored in the system.